MAKNA JODOH PENGANTAR JENAZAH GANTI JUDUL JODOH WASIAT BAPAK - Tsabit, Muhammad (Universitas Bina Sarana Informatika, 2017)
Broadcast began Â grown rapidly and dynamic. With the freedom of the press in Indonesia, many emerging companies engaged in mass media, especially television. Interesting program title becomes the selling point to win the competition. In an event there is a title that will raise the event because the title has a very important position. The key to successful event program is the title. The method used is descriptive method aims to explain factually and carefully. Data collection techniques conducted through interviews, the results of this study were analyzed using descriptive analysis techniques. The results showed that. The title of television programs is very influential. The conclusion of this study is that the program event title generally ignores the association with the theme, or irrelevant.Â Keywords: title, sinetron program, television